2011
DOI: 10.1126/science.1209389
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid 21 Lutetia: Low Mass, High Density

Abstract: 42The Rosetta flyby geometry at Lutetia on 10 July 2010 was suboptimal 43 because of the large flyby distance d=3168 +/-7.5 km, the high relative 46 Frequency Prediction 47The received carrier frequency from the actual flyby is compared with a 61The frequency prediction is routinely computed for radio science data 151The Doppler contributions from the HGA slew are evident in Figure 2b. 152The increase in frequency shortly before closest approach contrasts 174The rotation rates and angles were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 11 publications
(10 reference statements)
4
39
0
3
Order By: Relevance
“…Lutetia is an Xc-type asteroid (or M-type in the Tholen taxonomy), its bulk density was determined from the spacecraft Rosetta flyby as 3.4 ± 0.3 g cm −3 (Pätzold et al 2011). Rosetta also performed spectroscopy of Lutetia (Coradini et al 2011) and reported no absorption features in the spectral range from 0.4 to 3.5 µm.…”
Section: Lutetiamentioning
confidence: 99%
“…Lutetia is an Xc-type asteroid (or M-type in the Tholen taxonomy), its bulk density was determined from the spacecraft Rosetta flyby as 3.4 ± 0.3 g cm −3 (Pätzold et al 2011). Rosetta also performed spectroscopy of Lutetia (Coradini et al 2011) and reported no absorption features in the spectral range from 0.4 to 3.5 µm.…”
Section: Lutetiamentioning
confidence: 99%
“…The mass of Lutetia has been determined to be 1:700 AE 0:017 Â 10 18 kg (Pätzold et al, 2011), which gave a density of 3.4 ± 0.3 g/cm 3 (Sierks et al, 2011). Although Lutetia has been examined from Earth prior to this flyby (Belskaya et al, 2010), details of the taxonomy is limited, hindered by the complex surface composition (Barucci et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both current collisional models (Bottke et al 2005a;Morbidelli et al 2009) as well as the recent measurements performed by Rosetta on the asteroid Lutetia (Pätzold et al 2011;Sierks et al 2011) and by Dawn on the asteroid Vesta (Marchi et al 2012) minimize the possibility that large bodies (D > 100 km) are collisional fragments themselves; instead these objects are predominantly primordial (undisrupted) planetesimals, which means they are unlikely to have undergone a catastrophic disruption since their formation. Specifically, an impactor population capable of producing widespread collisional disruption among D = 100-200 km asteroids would 1. strongly affect asteroids like Vesta by creating ∼9-10 basinforming events equivalent to the one that made the D ∼ 500 km Rheasilvia basin.…”
Section: Surfaces Of S-type Asteroids As Exposed Interiorsmentioning
confidence: 99%